Assessment of FVIII, D-dimer, S. ferritin, and lactate dehydrogenase in hospitalized patients with 2019 coronavirus disease - Enaam Muhsin Hameed Al-Taie; Hind Shaker Al-Mamoori (Iraqi Journal of Hematology, 2021)
BACKGROUND: Corona virus disease 2019 (COVID-19) is a coronavirus that can produce a variety of symptoms, ranging from asymptomatic carrier status to severe respiratory failure, multiple organ dysfunction, and death, it might be associated with hypercoagulability as increase in coagulation factor 8 (FVIII). OBJECTIVES: This study was carried out to investigate markers of hypercoaguablility (factor VIII activity, D-Dimer) in hospitalized adult patients with COVID-19, evaluation of certain markers of inflammation (S. ferritin, lactate dehydrogenase [LDH], C-reactive protein [CRP], and erythrocyte sedimentation rate [ESR]) and correlate those markers with each other. PATIENTS AND METHODS: This cross-sectional study included 70 adult hospitalized patients with COVID-19. Blood samples were obtained for FVIII, D. dimer, and ESR. Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) version 23 and Microsoft Office Excel 2010. RESULTS: The mean age of enrolled 70 patients was 60.22 ± 14.43 years. 44 (62.9%) of patients had neutrophilia and lymphopenia was seen in 41 (58.6%). High ratio of N/L was seen in 66 (94.3%). Low count of eosinophil was seen in 44 (62.9%), high LDH level was seen at 57 (81.4%). Regarding serum ferritin, high level was seen 64 (91.4%) and high level of CRP was seen in 56 (80%). High level of ESR was seen in 64 (91.4%) and high level of D. dimer was seen in 55 (78.6%), while the high level of FVIII was seen in 30 (42.9%) and low FVIII level was seen in 4 (5.7%). CONCLUSIONS: The majority of patients had neutrophilia, lymphopenia, high N/L ratio, and eosinopenia. Markers of inflammation (S. ferritin, LDH, CRP, and ESR), which were elevated. FVIII level and D. dimer were elevated in the majority of patients with COVID-19. Few of the patients were had a low level of FVIII, which might be related to abnormal function of the liver or might be attributed to autoantibodies directed against FVIII.